CONSUMER TOUCHPOINT: INDONESIAN TOURISM DEVELOPMENT STRATEGY THROUGH IMPROVING THE QUALITY OF VISITOR SERVICES - Daud, Anshar; Affandi, Hanif Saputra; Juliana, Juliana; Syahputra, Muhammad Halfi Indra; Maulana, Muhammad Fikri (JURNAL ILMIAH EDUNOMIKA, 2024)
Abstract This research aims to determine (1) the role of improving the quality of visitor services on visitor satisfaction based on tourist reviews; and (2) strategies for developing Indonesian tourism through improving the quality of visitor services. This research uses SWOT analysis as an analytical tool to explore Indonesian tourism development strategies through improving the quality of visitor services. The results of this study show that (1) Tourist reviews after visiting tourist attractions are strong social evidence that can significantly influence potential tourists' decisions; and (2) Indonesia's tourism development strategy through improving the quality of visitor services consisting of the SO strategy through tourism promotion by offering quality visitor services, the WO strategy by developing a consumer touchpoint concept to attract tourists, the ST strategy through collaboration with tourism stakeholders to support consumer touchpoint tourism, and WT's strategy by educating tourism managers to improve the quality of visitor services. Keywords: Quality, visitor services, SWOT